1985
DOI: 10.2466/pms.1985.60.2.647
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Early School Achievement in Reading and Handwriting Using Major ‘Error’ Categories from the Bender-Gestalt Test for Young Children

Abstract: Errors by category and total errors on the Bender-Gestalt were used as school-entry predictors of later achievement in reading and writing in the primary school. After accounting for the effects of intelligence, apart from being related to ‘reading comprehension’ at Grade 1, die total errors made on the Bender were not a good predictor of later reading or writing performance. Circles for dots (a subcategory of the ‘distortion’ major error category) offered the most independent predictive value for later readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Besides, other studies also found correlations between IQ and handwriting speed McKay & Neale, 1985).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides, other studies also found correlations between IQ and handwriting speed McKay & Neale, 1985).…”
Section: Discussionmentioning
confidence: 90%
“…Finally, on the cognitive domain, previous studies have indicated that IQ and reading abilities are related to writing mechanics. A positive correlation between verbal IQ and writing speed as well as a negative relationship between total IQ and handwriting errors were observed McKay & Neale, 1985). Biemiller, Regan, and Gang (1993, as cited in Graham & Weintraub, 1996, p. 34) found a positive correlation between writing fluency and reading speed.…”
Section: Introductionmentioning
confidence: 91%
“…For children in grades 1 through 3, reported a correlation of .22 between handwriting speed and verbal IQ. McKay and Neale (1985) indicated that IQ was negatively correlated (-.37) to handwriting errors in their study with second grade children. As Harris (1960) noted three decades ago, intelligence is not a particularly good predictor of handwriting performance.…”
Section: Correlates Of Skill Development In Handwritingmentioning
confidence: 88%
“…This assumption, though, has received weak and ambiguous support in the research literature. McKay and Neale (1985), for example, found that scores on the Bender-Gestalt test in the first grade were of little value in predicting handwriting errors in second grade. Once the variance due to IQ was accounted for, only one of the Bender error categories, lines for dots, added significantly to the prediction of handwriting errors, accounting for just 4% of the variance.…”
Section: Correlates Of Skill Development In Handwritingmentioning
confidence: 99%
“…As relações entre leitura, escrita e desenvolvimento perceptomotor, no que concerne à aplicabilidade e validade do Bender como um instrumento preditivo dessas habilidades ainda não estão bem consolidadas na literatura. Sobretudo quando se consideram os resultados provindos de pesquisas realizadas com base no sistema de correção de Koppitz (Bandeira, & Hutz, 1994;Koppitz, 1975, Mckay, & Neale, 1985Nielsen, 1969;Nielson, & Sapp, 1991; para citar alguns). De maneira geral, os estudos realizados com base no Bender -Sistema de Pontuação Gradual (B-SPG), tanto com relação à leitura e à escrita, quanto à dificuldade de aprendizagem dessas habilidades, têm demonstrado a sensibilidade do sistema em diferenciar os indivíduos nas avaliações realizadas (Carvalho,& Noronha, 2009;Santos, Suehiro,& Vendemiatto, 2009;Suehiro, & Santos, 2005; Também no que concerne às idades dos participantes, a autora verificou diferenças estatisticamente significativas.…”
Section: Introductionunclassified